The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1111/j.1365-2559.1999.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant phyllodes tumours of the breast display increased stromal p53 protein expression

Abstract: Increased p53 immunoreactivity is present in malignant phyllodes tumours in contrast to benign phyllodes tumours and fibroadenomas. Malignant phyllodes tumours display a distinctive pattern of p53 immunostaining which may be of diagnostic value. These findings suggest that p53 protein may be important in the progression of benign to malignant phyllodes tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
32
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 8 publications
6
32
0
Order By: Relevance
“…Our results support those of a previous study, which showed that Ki-67 expression correlates with the histologic classification of PT (13). Our study also is in agreement with others in that p53 protein expression correlates with the histologic classification of PT (14,15). In our study, however, neither Ki-67 nor p53 expression correlated with clinical behavior.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results support those of a previous study, which showed that Ki-67 expression correlates with the histologic classification of PT (13). Our study also is in agreement with others in that p53 protein expression correlates with the histologic classification of PT (14,15). In our study, however, neither Ki-67 nor p53 expression correlated with clinical behavior.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies have suggested that Ki-67, a proliferation marker, and p53, a tumor suppressor gene, may be implicated in predicting behavior of breast carcinomas in general and of PT in particular (13)(14)(15). In addition, cytogenetic investigation has been performed in a small number of PT (16,17).…”
mentioning
confidence: 99%
“…In breast phyllodes tumors, the role of p53 has been fairly well investigated, 1,[16][17][18][19] with some authors suggesting a possible prognostic function, 16,18,19 while its predictive utility has not been validated by others. 1,17 It is stated that p53 immunohistochemical expression in stromal cells can be relied upon as an adjunctive tool in the diagnosis of malignancy in phyllodes tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of p53 expression in phyllodes tumors have focused primarily on stromal cells, 14,[16][17][18]25 with observation of perithelial accentuation of stromal cell staining. 14, 18 Feakins et al 1 mentioned that the epithelial component in their cases usually stained negatively, while in another two reports, p53 reactivity was described in the breast epithelium in conjunction with stromal staining, 26,27 and it was postulated that dual expression of p53 protein in both the epithelium and stroma reflected the existence of an interaction between these components, 26 akin to the conclusion of Sawyer et al, 28 who believed that both epithelium and stroma of phyllodes tumors were participants in the neoplastic process. Our finding of an association between p53 stromal staining with that in luminal and myoepithelium lends credence to this purported relationship, although the presence of myoepithelial staining and its possible role in this process is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation